1997
DOI: 10.1073/pnas.94.25.13997
|View full text |Cite
|
Sign up to set email alerts
|

Periplasmic superoxide dismutase protectsSalmonellafrom products of phagocyte NADPH-oxidase and nitric oxide synthase

Abstract: Superoxide dismutase (SOD) catalyzes the conversion of superoxide radical to hydrogen peroxide. Periplasmic localization of bacterial Cu,Zn-SOD has suggested a role of this enzyme in defense against extracellular phagocyte-derived reactive oxygen species. Sequence analysis of regions f lanking the Salmonella typhimurium sodC gene encoding Cu,Zn-SOD demonstrates significant homology to phage proteins, ref lecting possible bacteriophage-mediated horizontal gene transfer of this determinant among pathogenic bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
345
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 363 publications
(358 citation statements)
references
References 39 publications
10
345
0
1
Order By: Relevance
“…S. enterica serovar Typhimurium ATCC 14028s or its isogenic derivatives were used and grown in media as described (7,8). S. enterica CL1000 (recA) and S. enterica CL2001 (recBC) are described in ref.…”
Section: Methodsmentioning
confidence: 99%
“…S. enterica serovar Typhimurium ATCC 14028s or its isogenic derivatives were used and grown in media as described (7,8). S. enterica CL1000 (recA) and S. enterica CL2001 (recBC) are described in ref.…”
Section: Methodsmentioning
confidence: 99%
“…Peritoneal exudate cells from WT C57BL͞6 Nramp1 G169D (ity s ), TNFR-KO Nramp1 G169D (ity s ), and TNF␣-KO Nramp1 G169D (ity s ) mice (The Jackson Laboratory) were harvested 4 days after i.p. inoculation of 1 mg͞ml sodium periodate as described (19). Peritoneal exudate cells were resuspended in RPMI medium 1640 supplemented with 10% (vol͞vol) heat-inactivated FCS (Gemini Biological Products, Calabasas, CA)͞1 mM sodium pyruvate͞10 mM Hepes͞2 mM L-glutamine (all from Sigma-Aldrich).…”
Section: Methodsmentioning
confidence: 99%
“…The housekeeping E. coli enzyme and the Salmonella SodCII evidently serve to defend unidentified periplasmic targets from O 2 − that leaks from respiratory-chain components on the outer aspect of the cytoplasmic membrane (6). However, periplasmic SOD evidently plays an additional role in several bacterial pathogens, whom it helps withstand the oxidative burst of host macrophages (54) Initial surveys suggested that some obligately anaerobic bacteria lacked SOD (1)-raising the possibility that the lack of SOD was the feature that consigned them to anaerobic habitats. However, recent work has revealed that these organisms employ superoxide reductases, rather than dismutases, as scavengers (55,56).…”
Section: The Oxyr and Perr Regulators Of Responses To H 2 O 2 Stressmentioning
confidence: 99%